Israel in Europe - Abbott, G. F. (George Frederick), 1874-1947 (Salt Lake City, UT : Project Gutenberg, 2023)
"Israel in Europe" by G. F. Abbott is a historical account written in the early 20th century. The book explores the complex relationship between the Jewish people and European societies from ancient times to the modern era, addressing themes of persecution, cultural identity, and the Jewish Question. Abbott's work seeks to illuminate the trials and tribulations of Jews throughout history, making it a significant resource for those interested in Jewish history and European relations. The opening of the book sets the stage for a historical examination of the Jewish presence in Europe, beginning with the long-standing question of coexistence and the treatment of Jews in various regimes. Abbott introduces the concept of the Jewish Question and illustrates the enduring nature of Jewish identity amidst adversity and diaspora. He discusses how Jews have been variously integrated and marginalized throughout history, yielding a narrative that underscores both the resilience of the Jewish people and the prejudice they have faced over centuries, which continues to resonate in contemporary discussions about identity and belonging. (This is an automatically generated summary.)
Release date is 2023-09-29
Richard Hulse and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Jews -- History; Jews -- Europe